WT1 Gene Overexpression in Oncohematological Disorders: Theoretical and Clinical Aspects (Literature Review) - NN Mamaev; YaV Gudozhnikova; AV Gorbunova (Клиническая онкогематология)
The article discusses recent data on the WT1 gene overexpression phenomenon in patients with acute leukemias, myelodysplastic syndromes, chronic myeloid leukemia, non-Hodgkin’s lymphomas, and multiple myeloma. It demonstrates that monitoring of the WT1 gene overexpression proves to be effective during the posttransplantation period, as well as after the induction chemotherapy. This approach may be applied in diagnosing the minimal residual disease and early detection of leukemia relapses, as well as their timely and controlled treatment. There are other promising fields of research, such as testing autografts for the presence or absence of tumor elements, as well as evaluation of the efficacy of induction chemotherapy in high risk patients.